2018
DOI: 10.1002/jcc.25168
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of ANN‐based QSAR models for prediction of antioxidant activity of flavonoids

Abstract: Quantitative structure-activity relationships (QSARs) built using machine learning methods, such as artificial neural networks (ANNs) are powerful in prediction of (antioxidant) activity from quantum mechanical (QM) parameters describing the molecular structure, but are usually not interpretable. This obvious difficulty is one of the most common obstacles in application of ANN-based QSAR models for design of potent antioxidants or elucidating the underlying mechanism. Interpreting the resulting models is often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 64 publications
1
34
0
Order By: Relevance
“…Previously, several studies reported that the catechol moiety played a critical role in phenolic antioxidants . However, Woodman insisted on a minor role of the catechol moiety .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, several studies reported that the catechol moiety played a critical role in phenolic antioxidants . However, Woodman insisted on a minor role of the catechol moiety .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, all subtypes are composed of a dihedral angle between the B ring and the A/C fused rings. Thus, it is difficult to predict the ET (or antioxidant) potential of flavonoids, regardless of the amount of antioxidant structure–activity relationship studies …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative structure‐activity relationship models (QSAR models) apply the toolbox of chemometrics and chemoinformatics to predict the chemical, physical, or biological properties of chemicals based on a set of descriptor variables that describe the structure of the chemicals . The main areas of the application of QSAR models are the modelling of different biological activities (eg, antimalarial, antioxidant, and anti‐HIV), chemical properties (eg, chromatographic retention data and biodegradation), and toxic endpoints (eg, genotoxicity and hepatotoxicity). Moreover, besides predicting the properties of certain molecular structures, the inverse task, the design of molecular structures for certain properties is achieved as well, as these QSAR models are a time‐effective and economically friendly way to design new drugs .…”
Section: Introductionmentioning
confidence: 99%